The Power of International Collaboration in Advancing Haematology and Oncology: Fostering Excellence between the UK and Iraq. - Ahmed Al-Hassani (مجلة كلية الطب)
Modern international connectivity makes international cooperation essential for medical progress specifically in specialised medicine areas like haematology and oncology. Healthcare problems become more manageable when countries unite their expert knowledge with resources and creative solutions to achieve better patient results worldwide. The University of Baghdad should establish partnerships with UK healthcare organisations to address national healthcare deficiencies as they create mutual educational programs.